CULTIVATING TOURISM COMPETENCIES VIA ADDIE AND ACTION LEARNING IN FIRST-YYEAR HIGHER EDUCATION - Hung, Yu-Ting; Huang, Kan-Chung (International Journal of Application on Economics and Business, 2025)
This study adopts the ADDIE instructional design model as its core framework, integrating diverse teaching materials, to create a multisensory and cognitively engaging learning environment that fosters first-year university students’ motivation for reading and self-directed learning. The course further incorporates reciprocal teaching strategies to encourage students to build emotional connections between personal experiences and course content. Through peer and instructor dialogue, students are guided to develop critical thinking, respect for diverse perspectives, and interpersonal communication skills. Additionally, action learning is implemented through cross-context experiential activities such as field visits to historical sites, museum tours, and interactions with tourism professionals, enabling students to apply foundational tourism knowledge in authentic contexts and deepen their learning through reflection. Both quantitative and qualitative assessment tools are used to evaluate learning outcomes and shifts in student attitudes, informing ongoing instructional reflection and curriculum refinement. Overall, this pedagogical design effectively cultivates students’ aesthetic sensitivity, imagination, communication, and expression, while strengthening their foundational knowledge in tourism and capacity for autonomous learning. The study offers practical insights for competency-based and learner-centered approaches in higher education.